Presenting a Developed and Effective Model of Organizational Culture Regarding the Existing Problems and Challenges (A Case Study of Refah Bank of Iran) - SHABANI, HOSSEIN; POURKIANI, MASOUD; SALAJEGHEH, SANJAR; SAYADI, SAEED; BABAEI, HOJAT (The journal of contemporary issues in business and government, 2020)
Organizational effectiveness as the most significant objective of any organization is the goal that all organizational efforts are made to achieve. Thus, the aim of this paper is to provide a developed and effective model of organizational culture considering the existing problems and challenges. This research is applied in terms of purpose, descriptive of correlational type in terms of nature, and a survey in terms of method. The statistical population is the employees of the Refah Bank of Iran. The sample size was 344 people who were selected by stratified random sampling. A researcher-made questionnaire was used to collect information. The questionnaire of organizational culture was set up in 9 factors and 42 sub- dimensions (indices), the questionnaire of challenge and problem identification was set in 3 factors and 18 sub-dimensions (indices) and the questionnaire of organizational effectiveness was set in 4 factors and 28 sub-dimensions (indices). The face and content validity of the questions was confirmed by experts. Cronbach’s alpha coefficient was calculated higher than (0.7) which indicated the internal consistency of the items confirming reliability. In order to analyze the data, structural equation modeling was applied through using amos software. The results indicated a significant relationship between organizational culture and the identification of challenges and problems (p = 0.001, β = 0.486). Considering the positive path coefficient, this relationship is incremental (direct). The results also showed a significant relationship between identification of challenges and problems with organizational effectiveness (p = 0.001, β = 0.441). This relationship is incremental (direct). The results indicated that organizational culture indirectly and through identifying challenges and problems affects organizational effectiveness by the amount of (0.214). The rate of indirect effect through the identification of challenges and problems is equal to (0.214).